Decentralized k-anonymization of trajectories via privacy-preserving tit-for-tat - Domingo-Ferrer, Josep; Martínez, Sergio; Sánchez, David (Computer communications, 2022)
Mobility data, and specifically trajectories, are used to monitor the mobility of the population and are crucial to improve public health, transportation, urban planning, economic planning, etc. However, trajectories are personally identifiable information and hence they should be anonymized before releasing them for secondary use. Anonymization cannot be limited to suppressing the metadata containing the subject’s identity, because the origin, the destination and even the intermediate points of a trajectory may allow re-identifying the subject who followed it. Proper anonymization requires masking detailed spatiotemporal information. The standard approach to build anonymized data sets is centralized: the subjects send their original movement data to a controller, who takes care of producing an anonymized mobility data set. This requires subjects to blindly trust the controller. In this paper, we empower subjects with the ability to anonymize their trajectories locally by adhering to a privacy model in order to achieve formal privacy guarantees. After reviewing the state of the art, we motivate our choice of k-anonymity as a privacy model. We then set out to decentralize k-anonymity in a rational setting: a subject k-anonymizes her completed trajectory by aggregating with k−1 similar trajectories obtained from other (unknown) subjects. The latter trajectories are gathered via an anonymous and privacy-preserving tit-for-tat data exchange protocol, which runs on a fully decentralized peer-to-peer network. Experiments show that, without relying on a (trusted) data controller and while ensuring privacy w.r.t. other peers, our approach yields k-anonymized mobility data sets that are still reasonably useful compared to the near-optimal data sets obtained in the centralized approach.